Cote d'Ivoire : Poverty Reduction Strategy Paper; Joint Staff Advisory Note. (IMF Staff Country Reports; Country Report, 2009)
This Joint Staff Advisory Note focuses on the Poverty Reduction Strategy Paper (PRSP) for Cote d'Ivoire, and discusses poverty trends, the PRSP's strategic pillars, and key outcomes sought, including a sound macroeconomic framework, and monitoring and evaluation arrangements. IMF staff supports the authorities' plans to link the strategic priorities of the PRSP with budgetary allocations and processes. The IMF staff also agrees with the assessment of poverty made in the PRSP, and urges an immediate and focused effort to reverse the rising trend in poverty.